2017
DOI: 10.1377/hlthaff.2016.1204
|View full text |Cite
|
Sign up to set email alerts
|

Most Hospitals Received Annual Penalties For Excess Readmissions, But Some Fared Better Than Others

Abstract: The Hospital Readmissions Reduction Program (HRRP) initiated by the Affordable Care Act levies financial penalties against hospitals with excess thirty-day Medicare readmissions. We sought to understand the penalty burden over the program's first five years, focusing on characteristics of hospitals that received penalties during all five years, how penalties changed over time, and the relationship between baseline and subsequent performance. More than half of participating hospitals were penalized by the Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 23 publications
1
50
1
Order By: Relevance
“…In addition, the finding that by the end of our study period safety-net and highly penalized hospitals had lower disparities and, in the case of highly penalized hospitals, lower adjusted readmissions among Black patients than their counterparts suggests that this is not simply the case that hospitals that had the most room for improvement improved the most. On the other hand, of considerable concern is that safety-net hospitals have continued to receive higher penalties even though they have reached a major national policy goal (essentially eliminating disparities), 8 while hospitals that continue to have large disparities face much lower penalties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the finding that by the end of our study period safety-net and highly penalized hospitals had lower disparities and, in the case of highly penalized hospitals, lower adjusted readmissions among Black patients than their counterparts suggests that this is not simply the case that hospitals that had the most room for improvement improved the most. On the other hand, of considerable concern is that safety-net hospitals have continued to receive higher penalties even though they have reached a major national policy goal (essentially eliminating disparities), 8 while hospitals that continue to have large disparities face much lower penalties.…”
Section: Discussionmentioning
confidence: 99%
“…7 This has been a particular concern to policymakers since safety-net and teaching hospitals are much more likely to be penalized under the HRRP. 8,9 Thirty-day hospital readmissions have been associated with a variety of patient-related factors including medical complexity and sociodemographic factors. 10,11 Previous research has also shown that there are significant racial disparities in readmissions, even after adjusting for comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…; Sheingold, Zuckerman, and Shartzer ; Thompson et al. ). This higher penalty burden has raised concern that risk adjustment methods employed by the HRRP and VBP may not adequately account for the complexity and costs of treating socioeconomically vulnerable patients and, thus, lead to excessive financial penalties for hospitals treating these populations (Gilman et al.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…The most significant concern is the possible negative impact of the HRRP program on mortality, specifically for heart failure. Depending on the data source, statistical methodology for studying longitudinal trends and their association with the HRRP, and level of analysis (hospital vs aggregate national results), different studies have reached discordant conclusions regarding this crucial question …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with earlier predictions, a Kaiser Family Foundation report found that teaching hospitals have consistently had the largest proportion of programs penalized and the highest average penalties for the first 5 years of the program . Thompson et al found that between 2013 and 2017, major teaching hospitals, urban hospitals, and medium‐to‐large hospitals were more likely to be persistently penalized for all five of those years. Paradoxically, teaching hospitals have also consistently been shown to have superior mortality rates for index conditions including heart failure …”
Section: Introductionmentioning
confidence: 99%